2016
DOI: 10.1111/jicd.12223
|View full text |Cite
|
Sign up to set email alerts
|

Association between osteoporosis and periodontal disease among postmenopausal Indian women

Abstract: Skeletal BMD is related to clinical attachment loss, bleeding, and gingivitis, which suggests that there is an association between osteoporosis and periodontal diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 29 publications
0
19
0
1
Order By: Relevance
“…Existing data regarding the relationship between periodontal bone loss and osteoporosis are still inconclusive. The majority of studies evaluating the effect of systemic bone mineral density on periodontal bone loss found that low bone mineral density was significantly associated with an increase in loss of alveolar bone height and periodontal destruction, whereas other studies found no association . The controversial conclusion from these studies might be due to the differences in experimental designs, definitions of periodontitis and osteoporosis, as well as the different sample sizes.…”
Section: Discussionmentioning
confidence: 99%
“…Existing data regarding the relationship between periodontal bone loss and osteoporosis are still inconclusive. The majority of studies evaluating the effect of systemic bone mineral density on periodontal bone loss found that low bone mineral density was significantly associated with an increase in loss of alveolar bone height and periodontal destruction, whereas other studies found no association . The controversial conclusion from these studies might be due to the differences in experimental designs, definitions of periodontitis and osteoporosis, as well as the different sample sizes.…”
Section: Discussionmentioning
confidence: 99%
“…Kalinowski et al found a higher Fracture Risk Assessment Tool (FRAX) probability for fracture among patients with more severe periodontitis among men and women aged 40-89 years [18]. Another study by Richa et al found increased clinical attachment loss, bleeding, and gingivitis (all measures of PD) among postmenopausal women with OP compared to those without OP [15]. In a study examining PD in DM patients, deMiguel-Infante et al found significant associations between missing teeth, OP, and a higher risk for PD [16].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation, in addition to being associated with poorer glycemic control and increased risk for cardiovascular disease, is also associated with OP and increased fracture risk [9][10][11][12]. Furthermore, there is a known association between OP and PD [13][14][15][16]. PD, OP, and DM all share common risk factors like older age, inflammation, tobacco use, and stress but could also directly interact with one another.…”
Section: Introductionmentioning
confidence: 99%
“…Other researches have exhibited statistical significance in additional periodontal indices, concerning the inflammatory response of gingiva. Richa et al discovered that osteoporotic postmenopausal women suffer from more extensive gingival bleeding and dental plaque accumulation than those with normal BMD 46 . An other interesting parameter is the direct correlation between the severity of osteoporosis (usually measured through BMD) and the severity of chronic periodontitis.…”
Section: A Bidirectional Association Between Osteoporosis and Chronicmentioning
confidence: 99%